Modeling and analysis of a two-stage ORC for recovering waste heat of single flash geothermal cycle - Aryanfar, Yashar; Akhsheej, Arash; Ataei Sheykh, Kasra; Mousavi Ghasemlou, Shaban; García Alcaraz, Jorge Luis (CT&F - Ciencia, Tecnología y Futuro, 2021)
Reusing heat dissipation in thermodynamic cycles is an exciting proposal to increase efficiency. In this paper, a two-stage ORC (Organic Rankine Cycle) is proposed to recover and reuse wasted energy from an SFGC (Single Flash Geothermal Cycle). The working fluids studied for the recovery system include R227ea and R116 and R124 and R125. The effect of the main elements of system performance is investigated using sensitivity analyses. Exergy degradation of various components is also calculated. For working fluids R227ea and R116, the thermal efficiency improved by 7.66%, from 0.2023 to 0.2178. The system's thermal efficiency is improved from 0.2023 to 0.2177 by 7.61% using R124 and R125. The exergy efficiency of the initial working fluid improves by 15.04%, from 0.5044 to 0.5803. Further, the second pair of working fluids from 0.5044 to 0.5852, which indicates a 16.01% system efficiency improvement. 85% of the system exergy is eliminated through the expansion valve, turbine 3, heat exchanger 2, and mixer. Including the recovery phase in the base, SFGC will positively affect the power plant's performance.